Internet and Religiousness: The Examination of Indonesian Muslim Youth Population’s Use of the Internet - Shodiq Abdullah (Nadwa: Jurnal Pendidikan Islam, 2022)
Ease of access to information in the millennial era contributes to forming Muslim youth's unique and distinctive personalities and developing religious thinking. The current study aims to describe the use of the internet as a source of information on Islam and to identify the millennial Muslim youth's typology of religious thinking. The current research is a descriptive study using a mixed-method approach. The research subjects were 115 Muslim youths aged 17-21 living in Indonesia's Central Java province. The data were analyzed quantitatively using descriptive statistics and qualitatively using interpretive techniques. The results showed that millennial Muslim youths actively use the internet as a source of information to understand Islam. Most access Islamic content for an average of 30-60 minutes out of their 3-4 hours daily internet browsing time. Most respondents chose certain websites to find information and use it as a reference. Millennial Muslim youths have diverse religious thinking. Most respondents have a rationalist point of view regarding legal (fiqh) and Tafsīr. The respondents have diverse views on theology: Most have rationalists standing on the creation of man and the universe, and traditionalists standing on the theme of natural disasters and God's power.